Pengaruh Politik Dan Kekuasaan Terhadap Pembinaaan Atlet Dalam Dunia Olahraga Modern - Imel M Sihombing; Agustina Nababan; Gabriel Pasaribu; M.Rizki Hutabarat; Joice Tabita Arianti Ginting; Risky Alfi Sahri Hasibuan; Yan Indra Siregar; Putra Arima; Aldo Sahputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of politics and power on athlete development in the modern sports world. In the current development of sports, politics and power play a significant role in determining policies, funding, coaching systems, and athlete achievements at both national and international levels. The research method used is a qualitative method with a descriptive approach through literature studies from various journals, books, and relevant scientific sources. The results of the study indicate that political involvement can have positive impacts, such as increasing budget support, developing sports facilities, and establishing regulations that support athlete achievement. However, politics and power can also have negative impacts when there is excessive intervention, unfairness in athlete selection, and the existence of certain group interests that influence the sports development system. Therefore, professional, transparent, and achievement-oriented sports organization management is needed so that the sports world can develop optimally and fairly.